Dyskretny urok władzy – czyli kilka słów o tym dlaczego ulegamy wpływowi populistów? Perspektywa krytyczna - Karkowska, Magda (Studia Edukacyjne, 2021)
The book Critical Theory and Authoritarian Populism edited by Jeremiah Morelock was published by University of Westminster Press in 2018. It is not only a recent, but also an extremely up-to-date pu[1]blication due to the subject matter. The 299-page volume is divided into three chapters: “Theories of Authoritarianism”, “Foundations of Authoritarianism”, and “Digital Authoritarianism.” Within each of these, three, or in the case of the first chapter, four sections can be distinguished. Below, I will present the main themes of the book with reference to the political situation in Poland and Europe. From the pedagogical point of view, the developmental and educational implications of the issues discussed seem particularly important.